2009
DOI: 10.1002/pros.20987
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity reduces prostate carcinogenesis in a transgenic model

Abstract: BACKGROUND-Several epidemiological studies have reported an inverse association between physical activity and the risk of prostate cancer. To date, there are few animal studies looking at physical activity and cancer incidence, although the results are consistent with the epidemiological evidence. In general, as exercise intensity increased in the rats/mice, the likelihood that physical activity inhibited carcinogenesis increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 16 publications
2
24
0
1
Order By: Relevance
“…It is largely accepted that exercise training exerts a beneficial effect in some lymphomas and in colon, lung, endometrial, prostate and breast cancer [16][17][18][19][20][21][22][23]. Systematic reviews have concluded that the practice of physical activity in cancer patients improves important clinical (quality of life and fatigue) and physiological outcomes (muscle strength) [24].…”
Section: Introductionmentioning
confidence: 99%
“…It is largely accepted that exercise training exerts a beneficial effect in some lymphomas and in colon, lung, endometrial, prostate and breast cancer [16][17][18][19][20][21][22][23]. Systematic reviews have concluded that the practice of physical activity in cancer patients improves important clinical (quality of life and fatigue) and physiological outcomes (muscle strength) [24].…”
Section: Introductionmentioning
confidence: 99%
“…Our group previously identified physical activity as a potential modifiable factor associated with a reduced risk of prostate cancer progression and mortality (2, 3). In animal models, exercise has been shown to suppress solid tumor growth, progression, and metastasis (4-9). However, the underlying biological mechanisms are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In incidence studies, 58% reported that exercise inhibited tumor initiation or multiplicity (23–25, 27, 28, 31, 33, 35, 36, 41, 4346), 8% reported that exercise accelerated tumor incidence (26, 42), and 3% found null effects (29, 30, 32, 34, 3740). In the growth category, exercise was associated with tumor inhibition in 64% of studies (24, 39, 47–54, 5863, 6569), while 21% (37, 40, 44, 5557, 64) and 9% (26, 34, 42) of studies reported null and accelerated tumor growth, respectively.…”
Section: Resultsmentioning
confidence: 99%